Knowledge, attitudes and practices related to the influenza virus and vaccine among older adults in Eastern China. Issue 19 (3rd May 2018) - Wendlandt, Rachael; Cowling, B.J.; Chen, Yuyun; Havers, Fiona; Shifflett, Pat; Song, Ying; Zhang, Ran; Iuliano, Danielle; Xu, Cuiling; Yu, Hongie; Zhang, Jun; Zhang, Hongjun; et al.
Abstract: Background: This study aims to assess the association between socio-demographic and health characteristics of older adults in Eastern China and knowledge, attitudes, and practices (KAP) about the influenza virus and vaccine. Methods: A prospective cohort of 1506 older adults (aged ≥60 years) was enrolled from November to December 2015 in Jiangsu Province. We examined the association between demographics, health and functional status, and cognitive impairment at enrollment with awareness of influenza virus and vaccine and KAP items focused on five Health Belief Model domains. At a 12-month follow-up interview we assessed change in awareness and readiness to be vaccinated. Results: One in five older adults was aware of the influenza virus (21%) or vaccine (20%); even fewer reported having at least "a little" knowledge of the virus and vaccine (7% and 4%, respectively); less than 1% reported ever receiving an influenza vaccine. Retirement, higher education and income, and normal cognitive status were consistently associated with both awareness and knowledge of influenza virus. The odds of having at least "a little" knowledge of the vaccine was 2.9-fold (95% CI = 1.6–5.3) higher among older adults with at least some secondary schooling. Among the 108 with knowledge of the virus, 55% said they "worry about getting the flu this season." Among the 73 with knowledge of the vaccine, 92% believed the vaccine was at least somewhat effective and less than half (43%) thought that influenza vaccination was safe. At a 12-month follow-up interview, 33% (442/1333) increased from no knowledge to at least "a little". Conclusions: If and when influenza vaccines become widely available to older adults in China, our results indicate that influenza vaccination campaigns with basic information on the virus and vaccine could be beneficial for all older adults, especially those with less education and/or more cognitive impairment.